The use of agri-food labelling on the example of feta cheese and its unauthorised substitutes - Serlikowska, Agnieszka (Przegląd Prawa Rolnego, 2024)
The purpose of this article is to determine, using the example of controls on the naming of dishes with feta cheese and its unauthorised substitutes, whether the activities of the competent official control bodies meet the objectives set out in legislations of Member States and the EU’s legislation and, in particular, whether the indications in the content of administrative decisions imposing fines are not otherwise misleading. It is also an attempt to answer the question, whether taking over the competences of the Trade Inspection Office by the Inspection of Commercial Quality of Agricultural and Food Products has brought about changes regarding the nomenclature used by entities running catering outlets of the naming of dishes. In conclusion, the author states inter alia, that the names used by the relevant official food control authorities in their administrative decisions and communications to the media, do not help to create consumer awareness and confidence among businesses. The nomenclature used does not indicate the correct name of the product substituting feta cheese for another product, and sometimes it only gives it fancy name, thereby exposing traders to another administrative fine. This practice has not changed significantly after the competences of the Trade Inspection Office were taken over by the Inspection of Commercial Quality of Agricultural and Food Products.